Evaluasi Kebijakan Pengembangan UMKM di Kabupaten Majene: Pendekatan Realistic Evaluation - Hendrawan Hendrawan; Farhanuddin Farhanuddin; Pahruddin M (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This study aims to evaluate policies for the development of Micro, Small, and Medium Enterprises (MSMEs) in Majene Regency using the Realistic Evaluation approach with the context–mechanism–outcome (CMO) framework. The research employed a qualitative descriptive-exploratory method to gain an in-depth understanding of policy needs and implementation dynamics in local MSME development. Data were collected through in-depth interviews with relevant stakeholders, including local government officials, MSME owners, academics, financial institutions, and community representatives. The findings indicate that Regent Regulation Number 11 of 2020 and Regent Regulation Number 33 of 2022 contributed positively to sustaining the economic resilience of MSMEs during periods of crisis and post-crisis recovery. However, policy implementation remains largely administrative and top-down, limiting its capacity to promote sustainable business transformation. In the context dimension, low digital literacy, limited market accessibility, and weak institutional capacity reduced policy effectiveness. In the mechanism dimension, insufficient business mentoring and limited multi-stakeholder collaboration constrained the development of an adaptive empowerment ecosystem. In the outcome dimension, the policies mainly generated short-term improvements in productivity and economic stability without significantly strengthening competitiveness and entrepreneurial self-reliance.